Role of banking structure for achievement of monetary policy targets in Pakistan - ABBAS, Zaheer (KDI School, 2016)
In case of Pakistan, empirical findings suggest that the conventional tool of monetary policy i.e. interest rate has not been successful to motivate the banking sector to play pivotal role to keep the inflation at desirable level for sustainable economic growth through lending to private sector. Only banks having foreign back with less than 10% share in overall banking industry shows their timely responsiveness to monitory policy shocks. Rest of the banking structure does not support the channel of transforming the monetary policy through bank lending to private sector.
Thesis(Master) --KDI School:Master of Public Policy,2016